Pengaruh Kecepatan Pengadukan Pada Sistem High Rate Algae Reactor Terhadap Spesific Growth Rate Mikroalga Dan Mixed Liquor Suspended Solid Dalam Palm Oil Mill Efluent - Fauzy Isnandar; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The stabilization pond system are used in almost all of palm oil mills in Indonesia. One of it disadvantages is that it disable to exploit the potential of microalgae. HRAR is a technology that is able to increase microalgae biomass, and with a consortium of microalgae-bacteria, the elimination of organic matter is increasing. This research aim by determined the effect of mixing velocity in the HRAR system towards the spesific growth rate of microalgae and mixed liquor suspended solid in POME. The research was carried out in batches for 7 days by using solar energy as a source of light. Mixing were operated 24 hours per day with by variations of mixing velocity was 16, 20, and 24 cm/sec. Based on the research results, the mixing velocity of 20 cm/sec was the best velocity for indigenous microalgae. The highest spesific growth rate of microalgae was 0,402/day and mixed liquor suspended solid values was 3625 mg/L .Keywords: High Rate Algae Reactor (HRAR), Mixing, Microalgae, Palm Oil Mill Effluents (POME).